Deceiving the sky : inside Communist China's drive for global supremacy - Gertz, Bill (Encounter Books, 2019)
"The United States' approach to China since the Communist regime in Beijing began the period of reform in the 1980s was based on a promise that trade and engagement with America would result in a peaceful, democratic state. Forty years later the hope of producing a benign People's Republic of China failed. The Communist Party of China deceived the West into believing that its system and the Party-ruled People's Liberation Army posed no threat. These misguided policies produced the emergence of a 21st Century Evil Empire more dangerous than a Cold War version in the Soviet Union. Successive American presidential administrations fooled by ill-advised pro-China policymakers, intelligence analysts and business leaders facilitated the rise not of a peaceful China but a threatening and expansionist nuclear-armed communist dictatorship focused on a single objective: Weakening and destroying the United States. Defeating the United States is the first step for China's rulers in achieving global supremacy under a new world order based on an ideology of Communism with Chinese characteristics. The process included technology theft of American companies that took place on a massive scale through cyber theft and unfair trade practices. The losses supported the largest and most significant buildup of the Chinese military that threatens American and allied interests around the world. The military threat is only half the danger as China aggressively pursues regional and international control using non-military force, including economic, cyber and space warfare and large-scale influence operations. Deceiving the Sky details the failure to understand the nature and activities of the dangers posed by China and what the United States can do in taking steps to counter the threats"--